Efficacy and safety of direct-acting antivirals for treatment of hepatitis C infected kidney transplant recipients; a meta-analysis - Wisit Cheungpasitporn; Charat Thongprayoon; Karn Wijarnpreecha; Ankit Sakhuja; Wonngarm Kittanamongkolchai; Jackrapong Bruminhent (Society of Diabetic Nephropathy Prevention, 2017)
The use of direct-acting antivirals (DAAs) for treatment of hepatitis C virus (HCV) infection has been shown to very effective. However, its efficacy and tolerability in kidney transplant recipients are unclear. A literature search was performed using MEDLINE, EMBASE, and Cochrane Databases from inception through January 2017. We included studies that reported crude numbers of kidney transplant patients who achieved sustained virological response (SVR) or developed adverse effects with DAA therapy. Pooled estimated rates of SVR at 12 weeks (SVR12) after DAA therapy and discontinuation rate of DAAs treatment with 95% confidence interval (CI) were assessed using a random-effect, generic inverse variance method. The study protocol is registered with PROSPERO (International Prospective Register of Systematic Reviews; no. CRD42017054575). Around, 24 studies with 892 kidney transplant recipients were included in the meta-analysis. The pooled estimated SVR12 rate with DAAs treatment for HCV among kidney transplant patients was 97% (95% CI: 95%-99%; I2 = 22%). The pooled estimated rate of discontinuation of DAAs treatment for HCV among kidney transplant patients was 2% (95% CI: 1%-3%; I2 = 0%). Reported treatment-related serious adverse events included bradycardia with syncope in the co-administration of sofosbuvir with amiodarone, pulmonary embolism, gastrointestinal bleeding, portal vein thrombosis, bacteremia, anemia particularly with regimens including ribavirin, and uncommonly increased serum creatinine. The findings of our study suggest excellent efficacy and tolerability profiles of DAA therapy for HCV infection in kidney transplant patient populations.